Mitochondrial Respiration Inhibition Suppresses Papillary Thyroid Carcinoma Via PI3K/Akt/FoxO1/Cyclin D1 Pathway - Chen, Bojie; Lei, Shuwen; Yin, Xinlu; Fei, Mengjia; Hu, Yixin; Shi, Yuan; Xu, Yanan; Fu, Lei (Frontiers in Oncology, 2022)
Papillary thyroid carcinoma (PTC) is the most common thyroid malignancy, but little is known regarding PTC metabolic phenotypes and the effects of mitochondrial activity on PTC progression. The great potential of mitochondria-targeting therapy in cancer treatment promoted us to use tool compounds from a family of Mito-Fu derivatives to investigate how the regulation of mitochondrial respiration affected tumor progression characteristics and molecular changes in PTC. L20, a representative of 12 synthetic derivatives, was chosen for mitochondrial inhibition experiments. Sample sections from PTC patients were collected and processed to explore potential molecular alterations in tumor lymph node metastasis. In vitro analyses were performed using human papillary thyroid carcinoma cell lines (K1&TPC-1), with the human normal thyroid follicular cell line (Nthy) as a control. K1 cells were injected into nude mice to generate an animal model. The mice were injected with normal saline or L20 at 20 mg/kg or 50 mg/kg every other day; their body weights and tumor volumes were also measured over time. To elucidate the resulting metabolic phenotype, we measured OCR and ECAR, cellular ATP levels, ROS production, and mitochondrial membrane potential. Wound healing and Transwell assays, cell cycle assays, real-time fluorescence quantitative PCR, Western blotting and immunohistochemical staining were performed to explore glycolysis-dominant metabolism in PTC. Cyclin D1 and mitochondrial complex IV were detected in tumor samples from PTC patients with lymph node metastasis (LNM). L20 showed dose-independent and reversible modulation of mitochondrial respiration in PTC. In addition to mitochondrial dysfunction and early apoptosis, G1/S phase arrest. Notably, reversible mitochondrial inhibition yield durable suppression of tumor proliferation, migration and invasion via the PI3K/Akt/FoxO1/Cyclin D1 pathway. In vivo experiments demonstrated that L20 has a good safety profile and specific restorative effect on mitochondrial activity in the liver. In addition, L20 showed anti-tumor effects, alleviated tumor angiogenesis, and improved thyroid function. Reversible inhibition of ATP production and durable suppression of PTC growth indicates that the downregulation of mitochondrial function has negative impact on tumor progression and LNM via the PI3K/ Akt/ FoxO1/ Cyclin D1 pathway. These results provide new insights into the anti-tumor potential and clinical translation of mitochondrial inhibitors.